The Performance of Reinforcement Concrete Beam Containing Palm Oil Fuel Ash (POFA) and Expanded Polystyrene (EPS) in Term of Strain and Stress - Wai, Chee Hou; Mohamad Hairi, Osman; Mohd Eizuddin, Mahyeddin (Progress in Engineering Application and Technology, 2022)
The concrete in the construry industry require advanced technology to overcome the problems of pollution emission and exploitation of natural resources, while palm oil fuel ash (POFA) and expanded polystyrene (EPS) which are left unhandled by the manufacturers and bring environmental impacts are ideal to be used in producing concrete bacause of their characteristics. The aim of this study was to investigate the potential of POFA and EPS to produce decent concrete which is lighter in weight. The objectives of this study were to compare the compressive strength, investigate the strain and stress performance, and determine the optimnum percentage of POFA and EPS replacement for reinforced concrete beam. The samples reinforced beams were designed to be 1000mm × 150mm × 150mm with replacement of 10% or 20% POFA and 10% EPS. Compressive strength test was carried up by using concrete cubes while strain and stress test was carried up using concrete beams. The workability of concrete mix replaced with POFA and EPS decreased as the percentage of replacement increased. The mass of the concrete beams decreased with the substitution of POFA and EPS. While 10% POFA replacement gave best performance in compressive strength and strain and stress of the concrete, the further increasing of the percentage of POFA and EPS showed decrease in performance, while concrete with 10% POFA and 10% EPS gave similar results as normal concrete. Although the performance did not improve much, it proved that it can maintain the performance while promoting waste products as materials to save cost and reduce environmental problems.